'We are looked down upon and rejected socially': a qualitative study on the experiences of trafficking survivors in Nepal - Pranab Dahal; Sunil Kumar Joshi; Katarina Swahnberg (Taylor & Francis Group, 2015)
Background: The successful reintegration of sexual trafficking survivors into Nepalese society is challenging. This paper aims to explore the trafficking process, abuses faced during sexual slavery,and the challenges faced by women and girl survivors for successful reintegration. Method: This exploratory study used qualitative methods to identify that poverty, illiteracy, lack of opportunities, and varied social stigma initiate the victimization process, and continuity of this vicious circle increases the risk for (re)entrapment. Result: The reasons for sexual trafficking have also become the reasons for restricting survivors from opportunities for growth and mainstreaming. Conclusion: Non-existent support systems, detachment from familial ties, being outcast by society, and an uncertain livelihood make reintegration difficult for survivors.